Ownership balance, supervisory efficiency of independent directors and the quality of management earnings forecasts - Yunling Song; Xinwei Ji; Chi-Wen Jevons Lee (China Journal of Accounting Research, 2013)
In the Chinese securities market, with its characteristics of influence through personal relationships (Guanxi) and underdeveloped standards of law and enforcement, can independent directors play the supervisory role expected by securities regulators? In this study we use the degree of precision and accuracy in corporate earnings forecasts as proxies for the quality of information disclosure by listed companies and examine the supervisory efficiency of independent directors with respect to information disclosure. Using data from 2007 to 2009, we find that in the absence of ownership balance, independent directors have a significant positive effect on the accuracy of management forecasts. In addition, the personal backgrounds of independent directors have specific effects on management earnings forecasts. Directors with certified public accountant (CPA) expertise significantly improve the precision of management forecasts. However, directors with industrial expertise significantly reduce the precision of management forecasts. In other words, having directors with CPA expertise improves the independence of boards, but having independent directors with industrial expertise has the opposite effect.
Keywords: M41; M48; G38; 650; Independent directors; Ownership balance; Forecast precision; Forecast accuracy